Blink detection and magnetic force generation for correction of lagophthalmos, with specific regard to implant compatibility testing. (2nd January 2022) - Coussa, Razek Georges; Lomis, Nikita; Antaki, Fares; Samle, Jason; Patel, Kavita; Christodoulou, George; Prakash, Satya; Oestreicher, James; Arthurs, Bryan
ABSTRACT: Purpose: The overall goal was to restore a normal and synchronous blink in unilateral lagophthalmos. We describe the biocompatibility profiling of a novel ferromagnetic implant used for electromagnetic eyelid force generation. Methods: A non-contact blink detection system and an electromagnetic stimulation system were designed and tested. A modified Lester-Burch speculum equipped with strain gauge technology was used in blinking force measurement. Samarium–cobalt magnets were prototyped and coated with parylene-C. Biocompatibility testing was performed using NIH/3T3 mouse fibroblast cells with MTT colorimetric assay cytotoxic quantification. Outcome Measures: Cellular viability and interleukin concentrations. Results: Our system was capable of detecting 95.5 ± 3.6% of blinks in various lighting conditions. Using our force measuring device, the difference between non-paralyzed and paralyzed orbicularis oculi (OO) for normal and forceful blinking closure was 40.4 g and 101.9 g, respectively. A 16.6 × 5.0 × 1.5 mm curved shaped samarium cobalt eyelid implant was successfully developed and showed a reproducible blink at 100 ms with full corneal coverage with external eyelid taping. Compared to gold weights, parylene-C coated samarium cobalt implants showed not only excellent cell viability (82.0 ± 4.9% vs. 88.4 ± 0.9%, respectively, p >  .05), but also below detection threshold for pro-inflammatory marker concentrations (interleukin-6 < 2 pg/mL and interleukin-10 < 3 pg/mL). Conclusions: We demonstrated excellent in-vitro biocompatibility of our parylene-C coated samarium cobalt implants. We believe that our novel approach can improve the quality-of-life of affected individuals and provides new understanding of blinking biomechanics.